Patent Exhaustion and Licensing in the Supply Chain - Jay Pil Choi; Heiko Gerlach (CESifo GmbH, 2024)
This paper analyzes private and social incentives to levy an ad valorem licensing fee in a supply chain governed by the legal principle of patent exhaustion. With perfect competition at the upstream and downstream stage, the choice of the licensing segment is irrelevant for the patent holder and consumers. When exactly one segment of the value chain is monopolistic while the other one is competitive, the patent holder prefers licensing at the monopolistic stage leading to an alignment of private and social incentives. With imperfect competition at both stages, excessive downstream licensing can arise. We demonstrate that charging licensing fees at both stages of the supply chain (“double-dipping”) can be profitable for the patent holder and beneficial for consumers. We discuss the implications of this result for the application of the patent exhaustion principle.
Keywords: D43; L41; L44; 330; patent licensing; supply chain; first sale doctrine; patent exhaustion; double-dipping